Microsoft Excel: a tool for research. - Luis Orlando Pérez González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Frequently, our professionals in their research activity, lack of some knowledge and skills to deal with strong as well as complex statistical systems like SPSS; even these last are not available occasionally, and they have to look for other partners help. Besides, sometimes Microsoft Excel is undervaluated as a tool for research. This software could be of much help for this aim. Excel is basically an electronic calculation sheet, but it is much more, it is a very good option to solve most statistical needs in our researches.